Effect of Waste Nitrile Latex on Temperature Susceptibility of Bitumen - Abu Bakar, Siti Khatijah (International Journal of Integrated Engineering, 2019)
Deterioration of bitumen performance is generally due to inadequate viscoelastic response to loading and temperature changes. The deficiency of bitumen urges the need in developing high-quality bitumen through bitumen modification technology. In order to confirm the quality of the bitumen, laboratory tests were generally conducted through empirical physical testing. However, empirical physical bitumen testing (i.e. penetration, softening point and viscosity) is insufficient to predict binder performance at high temperature. Therefore, rheology testing was performed to compensate the empirical testing using Dynamic Shear Rheometer (DSR) test. Isochrones plots, rutting parameter and failure temperature obtained from DSR testing result were analysed to investigate the temperature susceptibility response of the bitumen. At commencement, conventional bitumen PEN 60/70 was modified with waste nitrile latex additive using mechanical high shear mixer in the laboratory. The modified binders were then undergone a short-term aging process through rolling thin oven film (RTFO) test. The results of modified binder indicated that added waste nitrile latex results in better temperature susceptibility response with the improvement of stiffness and elastic behaviour at high temperature. The result also indicated that, the positive improvement upgraded the PG level to PG82, hence, showed its higher capability to resist deformation.